2003
DOI: 10.1021/jp0343640
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of Calcium Carbonate Observed In-situ by Combined Small- and Wide-angle X-ray Scattering

Abstract: The transformation of amorphous colloidal calcium carbonate into single microcrystals was observed in supersaturated solutions in situ. The observations are done by simultaneous time-resolved small-angle and wide-angle X-ray scattering experiments (TR-SAXS/WAXS) at a third generation synchrotron source. TR-SAXS/WAXS demonstrates that the particles generated by reaction of Ca 2+ and CO 3 2-ions are amorphous. The transformation of these amorphous CaCO 3 particles proceeds via dissolution and subsequent heteroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
147
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(157 citation statements)
references
References 25 publications
10
147
0
Order By: Relevance
“…[137] Even during the aggregation of clusters to amorphous but solid species, there appear to be liquid intermediates, which can transform to mesocrystals or single crystal-liquid hybrid particles exhibiting a soap film like texture or the typical minimal surfaces of liquids like the P-surface. [139] The corresponding time scales related to mesocrystal formation are even broader spanning from the sub-ms range for primary particle formation [140,141] to many hours of structural ripening, as observed for the (NH 4 ) 3 PW 12 O 40 example. [42] This spans at least about 8 decades in time (10 À3 -10 5 s).…”
Section: Discussionmentioning
confidence: 81%
“…[137] Even during the aggregation of clusters to amorphous but solid species, there appear to be liquid intermediates, which can transform to mesocrystals or single crystal-liquid hybrid particles exhibiting a soap film like texture or the typical minimal surfaces of liquids like the P-surface. [139] The corresponding time scales related to mesocrystal formation are even broader spanning from the sub-ms range for primary particle formation [140,141] to many hours of structural ripening, as observed for the (NH 4 ) 3 PW 12 O 40 example. [42] This spans at least about 8 decades in time (10 À3 -10 5 s).…”
Section: Discussionmentioning
confidence: 81%
“…Under such conditions, the rapid formation of a most soluble and disordered phase such as vaterite is kinetically favored (Sawada, 1998), in agreement with the Ostwald step rule (Sö hnel and Garside, 1992). It is noteworthy that other more soluble and disordered phases, like ACC, might form prior to vaterite, as reported by numerous authors Loste et al, 2003;Pontoni et al, 2003). Although neither the XRD nor the IR spectroscopic analyses showed any evidence of the presence of this phase in the precipitates, its presence in the very initial stages of the process cannot be dismissed.…”
Section: àmentioning
confidence: 75%
“…The nucleation and growth of metastable CaCO 3 polymorphs is commonly related to the predominance of kinetic factors over thermodynamic properties (Ogino et al, 1987;Sawada, 1998). High supersaturation levels at nucleation and the initial stages of growth result in the formation of ACC, vaterite and aragonite (Sawada, 1998;Bolze et al, 2002;Pontoni et al, 2003). In agreement with Ostwald's step rule (Sö hnel and Garside, 1992), these three crystalline forms ultimately transform into the more stable calcite via dissolution-crystallization reactions of various degrees of complexity (Fernández-Díaz et al, 2009).…”
Section: Introductionmentioning
confidence: 84%
“…Thus, zones depleted of ACC particles have often been observed adjacent to calcite crystals growing on solid substrates from suspensions of ACC. [ 31 , 32 ] Simultaneous SAXS/ WAXS studies of the transformation of ACC have demonstrated that the heterogeneous nucleation and growth of calcite on the walls of the reaction vessel is accompanied by dissolution of the ACC, [ 33 ] while measurement of the changes in the solution composition which occur on crystallization of ACC to vaterite and calcite also show that the solution composition (as expressed in the ion activity product) remains at the level of the least stable polymorph present. [ 16 ] The solution is therefore supersaturated with respect to calcite and vaterite during crystallization of the ACC to these phases, which demonstrates that the rate-determining step is the growth of the crystalline phases rather than dissolution of the ACC.…”
Section: Discussionmentioning
confidence: 99%